SOLUTION OF FREDHOLM INTEGRO-DIFFERENTIAL EQUATION BY VARIATIONAL ITERATION METHOD - Lanlege, D. I.; Edibo, F. M.; Omeiza, Momoh Sheidu (FUDMA JOURNAL OF SCIENCES, 2023)
The Variational Iteration Method is applied to solve Fredholm Integro-differential Equation. The initial approximation was selected wisely which satisfies the initial condition of the given Fredholm Integro-differential Equation. The numerical result was analyzed with the aid of Mat-Lab and Maple software’s and are compared with the exact solution to show the usefulness and efficiency of the Method. The results show that the Variational Iteration Method is very efficient, reliable and of high accuracy for solving Fredholm Integro-differential Equation when compared with the exact solution.